A note on the friction of different ropes in right whale (Eubalaena glacialis) baleen: an entanglement model - Cavatorta , Derek; Starczak , Victoria; Prada , Kenneth; Moore , Michael (J. Cetacean Res. Manage., 2023)
Entanglement in fishing gear, particularly fixed trap, constitutes a significant source of North Atlantic right whale (Eubalaena glacialis) mortality. Entanglements may initiate with rope fouling baleen plates before snagging other appendages. Low friction between rope and baleen may minimise the risk of a sustained, progressive entanglement. The friction of eight different rope types against right whale baleen was examined by measuring the tension as each rope was pulled through two baleen plates held underwater. Polypropylene rope generated less friction with the baleen than all other fibres tested, including nylon, polyester, and commercial sinking line (a polypropylene/polyester blend). Thus, new commercial floating line (3-strand polypropylene) generates less friction than new commercial sinking line, both of which are commonly used in the fixed gear industry. Therefore, minimising rope friction should be one of the design parameters for whale-safe fixed fishing gear. Further study is required on the impact of rope aging, mouth closing and operator safety before recommendations can be made to industry.